3-D interfacial stress analysis of adhesively bonded curved laminated FRP composite single lap joint. (2020) - Behera, Ranjan K.; Parida, S.K.; Das, R.R.
Abstract: According to the fracture mechanics concept, the distribution of three-dimensional (3-D) three major stresses, i.e. peel stress for mode I, direct shear stress for mode II and transverse shear stress for mode III, are computed at different interfacial layers on curved laminated FRP composite single lap joint (SLJ), subjected to different ply orientation in adherend with application of tensile load. The three interfacial adhesive layers have been considered as; bottom layer (in between lower adherend and adhesive layer), middle layer (mid plane of adhesive layer) and top layer (in between upper adherend and adhesive) for determining the critical location of damage initiation by using failure index criteria. The results show that the variations of peel stress and shear stresses in the overlap region are very complicated in nature and hence a 3-D finite element analysis (FEA) is recommended to have a clear visualization of these stress variations. A comparative analysis due to ply orientation of adherends of SLJ has been carried out. It has been observed that the adhesion failures (in between adherend and adhesive) are more dominated than cohesion failure (within the adhesive layer).